High-permeability graphene oxide and poly(vinyl pyrrolidone) blended poly(vinylidene fluoride) membranes: Roles of additives and their cumulative effects - Tran, T.T.V. (Elsevier B.V., 2021)
We prepared poly (vinylidene fluoride) (PVDF) based membranes via the phase inversion method to investigate the individual and simultaneous effects of graphene oxide (GO) and poly (vinyl pyrrolidone) (PVP) additives. It was demonstrated that the noticeable contribution of GO was to lower membrane surface charge. The principal role of PVP was to enhance membrane porosity, Î±-to-Î² phase transformation and mechanical strength. PVP also assisted GO distribution in the membrane matrix owing to their hydrogen-bonding interactions. GO-PVP-PVDF membrane showed cumulative effects in membrane physicochemical properties. In both pure water and naphthol blue black (NBB) dye solutions at pHs 4â10, the filtrate permeance increased from the pure PVDF to GO-PVDF, PVP-PVDF and GO-PVP-PVDF membranes. Therein, GO and PVP introduction provided permeance increases by one order of magnitude. All the membranes exhibited high dye rejections of â¥80.0 due to the Donnan exclusion mechanism. The membranes showed negligible dye adsorption. The stable filtration performance was demonstrated over 24-h multi-cycle filtration. The GO-PVP-PVDF membrane achieved outstanding high permeance (953â1350 L mâ2 hâ1 MPaâ1) and excellent dye removal efficiencies (83.2â87.5), which opened an avenue for application of this PVDF composite membrane to actual dye wastewater treatment. Â© 2020 Elsevier B.V.